Detection of Gastroesophageal Reflux Esophagitis Using 2-fluoro-2-deoxy-d-glucose Positron Emission Tomography. (31st July 2012) - Tsai, Min-Kuei; Ding, Hueisch-Jy; Lai, Hsueh-Chou; Yen, Kuo-Yang; Li, Chia-Ing; Lin, Yu-Yi; Cheng, Kai-Yuan; Wang, Keh-Bin; Kao, Chia-Hung
Abstract : Background . Gastroesophageal reflux disease (GERD) is a common disease and a major upper gastrointestinal problem. The purpose of the present study is to evaluate the use of noninvasive 2-fluoro-2-deoxy-d-glucose positron emission tomography (FDG-PET) to detect gastroesophageal reflux esophagitis. Materials and Methods . This is a retrospective study reviewing 408 healthy check-up subjects (169 females and 239 men), who underwent both FDG-PET and upper gastrointestinal endoscopy during September 2008 to December 2009. Quantitative analysis of FDG uptake in the distal part of the esophagus was performed by calculating the maximum standard uptake value (SUVmax). This indicated the degree of esophagitis. FDG-PET findings were compared with endoscopic (modified version of the Los Angeles classification) diagnoses as the gold standard. Results . The SUVmax ranged from 1.30 to 3.40 in normal subjects and from 1.30 to 4.00 in subjects with gastroesophageal reflux esophagitis. In the esophagitis group, the SUVmax was 2.13 ± 0.42 in subjects with modified LA grade M, 2.21 ± 0.45 in subjects with LA grade A, and 2.48 ± 0.44 in subjects with LA grade B and C gastroesophageal reflux esophagitis. One-way ANOVA and post-hoc comparison with Bonferroni correction (P value = 0.003) identified statistical differences between the three groups. Conclusion . Noninvasive FDG-PET may be useful in the detection and evaluation of various degrees of gastroesophageal reflux esophagitis.